Real-time imaging reveals radiation-induced intratumor apoptosis via nutrient and oxygen deprivation following vascular damage - Go Kagiya; Ryohei Ogawa; Toshihide Matsumoto; Fuminori Hyodo; Nanako Abe; Ami Yuzawa; Haru Takeuchi; Miki Aoyagi; Ayaka Sato; Kei Yamashita; Masanori Hatashita (Molecular Therapy: Oncology)
Radiotherapy exerts significant effects on the tumor microenvironment. Radiation is known to induce direct tumor cell death through intrinsic factors (e.g., DNA repair activity and p53-mediated radiation sensitivity). It also induces indirect cell death by altering the tumor microenvironment. However, current knowledge is based on indirect evidence. We focused on apoptosis, a form of cell death, to elucidate the mechanisms underlying radiation-induced apoptosis in tumors. Using apoptosis-imaging cells and real-time imaging technology, we investigated the pathways involved in radiation-induced apoptosis in the tumor environment and found that the mechanism triggering early apoptosis following X-ray exposure involves minimal participation of the immune system. Furthermore, we demonstrated that apoptosis in tumors is an indirect form of cell death as well, primarily driven by radiation-induced damage to the tumor vasculature, which leads to reduced blood flow, resulting in nutrient and oxygen deprivation within cancerous tissue, which induces apoptosis. The presence of nutrient deprivation and hypoxia, mediated by tumor vascular damage, suggests the possibility of inducing not only apoptosis but also other forms of cell death (e.g., autophagic cell death and necrosis-like cell death) based on these mechanisms. These pathways provide valuable insights for the development of more effective radiotherapy strategies.